The role of play in shaping early childhood character: A systematic literature review - Didi Suryadi; Zsolt Németh; Julian Dewantara; Muhammad Daffa Haidar; Nur Khozanah Ilmah (Journal of Applied Movement and Sport Science, 2025)
Background. Early childhood character development plays a crucial role in the educational process. However, in practice, it is often overlooked. The concept of "learning through play and playing while learning" is fundamental to children's education. Play serves as a vital tool for stimulating various aspects of child development, including religious and moral values, cognitive abilities, language skills, social-emotional growth, physical-motor skills, and artistic expression.Objectives. This study aims to explore the role of play in fostering character development in children. Providing children with opportunities to engage in play allows them to internalize positive character traits effectively.Methods. This study employs a library research approach, utilizing secondary data obtained from previous studies rather than direct observations. A total of 13 national journals discussing children's character development were analyzed. These journals were sourced from Google Scholar using the keyword (“children's character development”).Results. Based on the reviewed literature, it can be concluded that play is highly effective in fostering children's character development. The findings highlight three key aspects: (1)The role of play and physical activities in shaping children's character.(2) The importance of character development in early childhood.(3) The influence of education and parental involvement in character-building.Conclusion. The study results indicate that integrating play into sports-based learning significantly contributes to early childhood character formation. Through sports, children develop essential values such as responsibility, mutual respect, perseverance, teamwork, and integrity.